The Evolving Political Marketplace: Revisiting 60 Years of Theoretical Dominance Through a Review of Corporate Political Activity Scholarship in Business & Society and Major Management Journals. Issue 5 (May 2022) - Lenway, Stefanie; Schuler, Douglas; Marens, Richard; Werner, Timothy; Green, Colby
We review articles about corporate political activity (CPA) published in Business & Society since its beginnings 60 years ago and in a set of other leading management journals over the past decade. We present evidence that most studies of CPA use the political markets' perspective. Under the premise that the contemporary political environment has changed significantly since the inception of the political markets' perspective, our review asks two interconnected questions. First, to what degree have changes in the political environment challenged the ability of the political markets' perspective to understand the pillars of politics: issues, institutions, interests, and information? Second, to what degree have CPA scholars augmented or diversified their theoretical arguments to accommodate these changes in the political environment? We document the CPA literature across these dimensions and questions and note that many scholars are already adopting other theories side by side with the political markets' perspective.